The Role of Ma'arif Nahdlatul Ulama Educational Institutions in the Development of Islamic Education in Indonesia (1926-1959) - Kholil, Muhamad; Ansori, M Afif; Andari, An An; Pribadi, Joko; Sudarmin, Sudarmin (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This research aims to examine the role played by Ma'arif Nahdlatul Ulama (NU) Educational Institutions in depicting the dynamics of Islamic education development in Indonesia. The focus of this research is to analyze the contribution of these educational institutions to the evolution of the Islamic education system, both in terms of curriculum, teaching methods, and their impact on student character formation. The research method includes historical analysis discussing the history and development of Ma'arif NU Educational Institutions since their establishment. The main data sources involve historical documents, archives, and interviews with key actors in these educational institutions, such as teachers, students, and administrators. The results of this research are expected to provide a comprehensive overview of how the role of Ma'arif NU Educational Institutions has shaped and influenced the context of Islamic education in Indonesia. Additionally, this research will also discuss the challenges and opportunities faced by these educational institutions in responding to the changing times and evolving educational demands.